Astrological Biochemistry of Vitamins - Dimri, Mayank; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
Vitamins are organic compounds and an integral part of the balanced diet. Biochemically they function as coenzymes. The vitamins belong to the zodiacal sign Virgo in astrological parlance. They complement medicine by the application of astrological knowledge for the eradication of aliments.